Perceived Organizational Support in Nepalese Banks - Lamichhane, Binita; Neupane, Dasarath (International Journal of Atharva, 2023)
This research study aims to investigate the perception of employees regarding organizational support in Nepalese commercial banks. The study used a survey design with a quantitative research approach to sample 120 bank employees. Data collected from the questionnaire were examined and interpreted using a variety of statistical techniques, including means, standard deviations, frequencies, and correlation analysis. The study explores the relationship between perceived organizational support and employee attitudes and behaviours. The findings provide valuable insights into the state of organizational support within the banking sector in Nepal. This report concludes by summarizing the key findings and implications for both researchers and practitioners.